The study on factors influencing e-learning readiness towards local university students in Malaysia - Dinish Ananthan; Nabilah Ramli; Ng Chun Siong; Nur Zakiah Mohd Yahya (2023)
E-learning is quickly expanding as a field of study and application. At the individual teacher and institutional levels, educators are experimenting with online teaching techniques across disciplines and topics. As a result of their parents' familiarity with digital technology, today's students have been dubbed "digital natives." All educational institutions changed their teaching strategies to online platforms during the 2020 COVID-19 pandemic. Get ready for online learning. However, it is unclear how this will impact students' readiness for online education. This study looked at how well-prepared students were for online learning at prestigious tertiary institutions in Malaysia. Therefore, this study aimed to study the Factors Influencing E-learning Readiness towards students’ academic achievement at local universities in Kelantan. This study employed the non-experimental quantitative research design. This research design is questionnaire. There are several questions have been asked in the questionnaire based on the dependence variables and independent variable of this study. The questionnaire is also collected the data of respondents which is the demographic information. Data were gathered from a sample size of 384 respondents from different universities. The data was analyze by using the statistical package for sciences (SPSS) version 27 software model measurement to determine the validity and reliability of analyses, demographic information analyses, descriptive analysis, normality test and hypothesis test. The results concluded all the independence variable of students’ characteristics factors, evaluation use of technology factors, institutional support factors, online interaction and social factors and perceived usefulness factors have a significant relationship with the E-learning readiness towards students’ academic achievement at local universities in Malaysia. All independent variables have the significant relationship to dependent variable as normality test are rejected and correlation are positive. The recommendation are improve the research technique on qualitative approach and identify the challenges of students face during their studies in addition to the impact of e-learning by future research.